Posthuman Literacy Practices in a Reggio-inspired South African school - Chambers, Lynn (School of Education, 2021)
Through a posthuman approach to literacy education, I explore the Reggio Emilia pedagogy adopted by an independent South African primary school. Unlike the current emphasis in literacy pedagogy on language, standardised and individualised testing and universal curriculum approaches, Reggio Emilia pedagogy views child, learning and knowing not as separate from each other and from the world, but as entangled and always on the move. Moreover, Reggio Emilia-inspired schools celebrate the ‘hundred languages' of children, not just the spoken or written word, and involve children in an emergent curriculum through pedagogical documentation. In my study, pedagogical documentation (including photos and videos) also serves as research ‘instrument' to co-create data and is analysed diffractively – drawing on feminist philosophers and scientists Donna Haraway and Karen Barad. The new theorypractice produced reconfigures literacy as an assemblage which includes human and nonhuman in an entangled, intra-acting becoming-together. This includes children, no longer understood as individual entities in the world, but as phenomena. My enquiry produces a rich entanglement of unexpected actors, including digital and non-digital technologies, discourses about literacy, questions of ethics and response-abilities, and many more. The ethics of a posthumanist orientation to literacy education urges us to think about what is made to matter in a classroom and what is excluded from mattering. My research shows that children, rather than having agency as singular entities, are part of distributed agency in learning and as such are rendered capable as part of a complex, living system always in motion.